2019
DOI: 10.1111/chso.12322
|View full text |Cite
|
Sign up to set email alerts
|

Child Protection in Voluntary Sports Clubs in Germany — Factors Fostering Engagement in the Prevention of Sexual Violence

Abstract: Based on the theoretical framework of organisational capacity and using data from an online survey of 8571 sports clubs in Germany, this study investigates clubs’ engagement towards child protection and the prevention of sexual violence. Only half of the clubs indicate that the prevention of sexual violence is a relevant topic for them, and on average, the clubs have implemented between two and three prevention measures. Pertaining to organisational capacity, human resource capacity (e.g. share of volunteers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Dummy variables ( IL_integrative, IL_youth, IL_performance, IL_conviviality , and IL_service ) that took on the value of 1 when the mean value of the underlying items was greater than 3.5 were formed (Table 2). Respective dummies have been used in previous studies in the same or similar way (Rulofs et al, 2019). This operationalization allowed VSCs to follow none, one, or multiple institutional logic(s).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dummy variables ( IL_integrative, IL_youth, IL_performance, IL_conviviality , and IL_service ) that took on the value of 1 when the mean value of the underlying items was greater than 3.5 were formed (Table 2). Respective dummies have been used in previous studies in the same or similar way (Rulofs et al, 2019). This operationalization allowed VSCs to follow none, one, or multiple institutional logic(s).…”
Section: Methodsmentioning
confidence: 99%
“…An already integration or youth-oriented VSC may demonstrate higher engagement levels concerning integrating refugees because it might have experience with inclusionary efforts toward other marginalized groups of society (Michelini et al, 2018; Vandermeerschen et al, 2017). Rulofs, Feiler, Rossi, Hartmann-Tews, and Breuer (2019) argue that a VSC’s degree of professionalization—represented by a service-oriented logic—might generally contribute to a higher awareness of societal issues. The studies of Michelini et al (2018) and Seiberth et al (2018) suggest that the institutional logic traditional/conviviality is in contrast to pursuing the goal of integrating refugees due to a low ambition to change well-established patterns of the organizational activities and/or the membership structures.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Research on the prevalence and nature of sexual violence in elite and recreational sport has increased remarkably since the beginning of the twenty-first century. Celia Brackenridge's pioneering contributions in the mid-1990s (e.g., Brackenridge, 1994Brackenridge, , 1997Brackenridge and Kirby, 1997) called for researchers around the globe to investigate this topic, with the aim to quantify the prevalence of interpersonal violence in sport, identify risk factors for its emergence, and develop and evaluate guidelines for improved safeguarding of athletes (e.g., Lang and Hartill, 2015;Rulofs, 2015;Vertommen et al, 2016;Hartill, 2017;Bjørnseth and Szabo, 2018;Ohlert et al, 2018;Rulofs et al, 2019b). Studies investigating the causes of the emergence of sexual violence have pointed out specific conditions in the field of sport, such as unequal gender relations and the social structures of competitive sport.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that few protection measures are evidence-based or built on theory, and they are rarely evaluated to determine whether the intended outcomes have been achieved (Parent and Hlimi, 2013 ; Hartill and O'Gorman, 2014 ; Lang and Hartill, 2014 ; Gurgis and Kerr, 2021 ). According to the literature, the implementation of policy has not kept pace with policy development, which created a problematic gap between policy and practice (Brackenridge, 2002 ; Parent and Demers, 2011 ; Donnelly et al, 2016 ; Rulofs et al, 2019 ; Kerr et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%